605 Sleep problems are associated with behavioral problems and decreased quality of life in children with Fontan circulation. (3rd May 2021) - Robertson, Kirstin; Seckeler, Michael; Klewer, Scott; Hsu, Chiu-Hsieh; Edgin, Jamie; Provencio-Dean, Natalie; Lopez, Silvia; Parthasarathy, Sairam; Combs, Daniel
Abstract: Introduction: Children with congenital heart disease who undergo a Fontan procedure are at higher risk of behavior and attention problems as well as reduced quality of life compared to age-matched peers. While sleep problems are associated with behavior and attention problems in children without Fontan circulation, this relationship has never been examined in children with Fontan circulation. We hypothesized that sleep problems in this population may increase the risk of behavior problems and also reduce health related quality of life (HRQOL). Methods: We analyzed data from the Pediatric Heart Network Fontan cross-sectional study to evaluate associations between a parent-reported diagnosis of a sleep problem with reported behavioral concerns and HRQOL as measured by the child health questionnaire (CHQ) in 558 children with Fontan circulation. Analysis was performed using logistic regression or Wilcoxon sum rank test, as appropriate, with Bonferroni correction for multiple comparisons. Results: Parent-reported sleep problems were present in 10% of participants. Sleep problems were associated with a 4.6x higher risk of attention problems, 10.2x higher risk of anxiety problems, 3.9x higher risk of behavioral problems, 9.5x higher risk of depression, 5.0x higher risk of developmental delay, 6.9x higher risk of learning problems and 2.2x higher risk of speech problems (p=0.04 for speech problems, p<0.001 for all others). Parent report of a sleep problem was associated with decreased physical HRQOL (z-score -1.3 [interquartile range-2.2, -0.2] vs 0.0 [-0.8, 0.4], p<0.001) and psychosocial HRQOL (-0.9 [-1.9, 0.0] vs 0.0 [-0.8, 0.7], p<0.001) compared to children without a reported sleep problem. Report of a sleep problem was associated with significantly lower HRQOL across all subdomains of the CHQ (p<0.05 for all subdomains). Conclusion: Children with Fontan circulation with sleep problems have an increased risk of behavioral and developmental problems as well as reduced HRQOL. Better understanding of sleep problems is needed in children with Fontan circulation, as sleep disorders may represent a reversible cause of behavioral problems and decreased HRQOL in this population. Support (if any): Funding to DC from the American Heart Association, University of Arizona Health Sciences Center, and NIH-NHLBI. Fontan study data obtained from the Pediatric Heart Network.